Mental Health of Parents and Preschool-Aged Children During the COVID-19 Pandemic: The Mediating Role of Harsh Parenting and Child Sleep Disturbances - Wang, Peiyao; Sun, Xiaoning; Li, Wen; Wang, Zijing; He, Shan; Zhai, Feng; Xin, Yuan; Pan, Linlin; Wang, Guanghai; Jiang, Fan; Chen, Jie (Frontiers in Psychiatry, 2021)
In the context of the coronavirus disease-2019 (COVID-19) pandemic, mental health problems of parents and children have become a public issue. Herein, we explored the association between parental well-being index and child mental health problems during the pandemic and the mediating role of harsh parenting and child sleep disturbances. An online survey was conducted among 16,398 parents of children aged 3–6 years (48.1% girls, Mage = 4.69 years, SDage = 0.75 years) from March 15 to 29, 2020. Child mental health (Strengths and Difficulties Questionnaire, SDQ), sleep problems (Children's Sleep Habits Questionnaire, CSHQ), and parental well-being index (World Health Organization-Five Well-Being Index, WHO-5), and harsh parenting were reported by parents. The results revealed that a higher parental well-being index was associated with lower child mental health problems. Harsh parenting and child sleep problems were significant mediators within the association. This study indicates the association between parental well-being index and child mental health during the pandemic and underlying mechanism, and has important implications for reducing parental and child mental health problems.